2011
DOI: 10.3324/haematol.2011.048231
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter phase II trial of decitabine as first-line treatment for older patients with acute myeloid leukemia judged unfit for induction chemotherapy

Abstract: The online version of this article has a Supplementary Appendix. BackgroundThe treatment of acute myeloid leukemia of older, medically non-fit patients still poses a highly unmet clinical need, and only few large, prospective studies have been performed in this setting. Given the established activity of hypomethylating agents such as 5-aza-2'-deoxycytidine (decitabine) in myelodysplastic syndromes and acute myeloid leukemia with 20-30% bone marrow blasts, we investigated whether this drug is also active in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
161
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(171 citation statements)
references
References 46 publications
(70 reference statements)
9
161
0
Order By: Relevance
“…Not surprisingly, a complex karyotype thus scores in the very highrisk cytogenetic groups of AML and MDS [2][3][4][5]. Notably, it recently became apparent that clofarabine and the DNA hypomethylating agents azacytidine and decitabine (DAC) have marked activity in complex-karyotype AML [6][7][8][9] and MDS [10][11][12][13][14][15][16]. However, it is unclear why these drugs differ from cytarabine and other cytotoxic agents in that regard.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, a complex karyotype thus scores in the very highrisk cytogenetic groups of AML and MDS [2][3][4][5]. Notably, it recently became apparent that clofarabine and the DNA hypomethylating agents azacytidine and decitabine (DAC) have marked activity in complex-karyotype AML [6][7][8][9] and MDS [10][11][12][13][14][15][16]. However, it is unclear why these drugs differ from cytarabine and other cytotoxic agents in that regard.…”
Section: Introductionmentioning
confidence: 99%
“…Since the large phase II DAC trial 00331 had recruited 54 CK+ patients, their outcome was compared with regard to the presence (MK+/ CK+, n = 37) or absence (MK−/CK+, n = 17) of the monosomal karyotype [8]. Intriguingly, the response rate was superior in the MK+/CK+ AML patients compared to MK−/CK+ patients (complete plus partial remissions 37 vs. 12 %).…”
Section: Introductionmentioning
confidence: 99%
“…HMA inhibit epigenetic silencing of cell-cycle regulatory elements and tumor suppressor genes, thus suppressing the reversible epigenetic changes that play a major role in pathogenesis of leukemogenesis [13][14][15][16]. Two agents, decitabine (Dec) and azacitidine (Aza), have been approved for the treatment of patients with myelodysplastic syndrome (MDS) and have been well tolerated in elderly individuals, leading to multiple clinical trials evaluating their use in older AML patients [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. The earliest clinical data of HMAs in AML patients were noncomparative trials mostly involving individuals unfit for IC [17][18][19][20]25].…”
Section: Introductionmentioning
confidence: 99%
“…Two agents, decitabine (Dec) and azacitidine (Aza), have been approved for the treatment of patients with myelodysplastic syndrome (MDS) and have been well tolerated in elderly individuals, leading to multiple clinical trials evaluating their use in older AML patients [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. The earliest clinical data of HMAs in AML patients were noncomparative trials mostly involving individuals unfit for IC [17][18][19][20]25]. Next, subgroup analyses of large prospective phase III trials of Aza or Dec demonstrated superior outcomes for HMA over best supportive care in AML patients with marrow blast counts of 20-30% [21,30,33].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested associations between the response to decitabine and genetic aberrations (e.g., monosomal karyotype, TET2 mutations), mRNA or microRNA expression, or DNA methylation [25][26][27][28][29][30][31][32]. Unfortunately, we did not have sufficient material to investigate molecular markers in our cohort.…”
Section: Survival In Subgroups Of Raebt Patientsmentioning
confidence: 93%